The Developing World's Bulging (but Vulnerable) Middle Class - Ravallion, Martin (2012)
Western notions of the 'middle class' are of little obvious relevance to developing countries. Instead, the middle class is identified here as those living above the median poverty line of developing countries, even if still poor by rich-country standards. Over 1990-2005, economic growth and global distributional shifts allowed an extra 1.2 billion people to join the developing world's middle class. Four-fifths came from Asia, and half from China. Many of those in this new middle class remain fairly close to poverty. Only 100 million of the 1.2 billion would not be considered poor in any developing county. Economic growth typically came with an expanding middle class.